2007
DOI: 10.1029/2006jc003770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aragonite saturation, temperature, and nutrients on the community calcification rate of a coral reef

Abstract: [1] In this study we investigated the relations between community calcification of an entire coral reef in the northern Red Sea and annual changes in temperature, aragonite saturation and nutrient loading over a two year period. Summer (April-October) and winter (November-March) average calcification rates varied between 60 ± 20 and 30 ± 20 mmolÁm À2 Ád À1 , respectively. In general, calcification increased with temperature and aragonite saturation state of reef water with an apparent effect of nutrients, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
208
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(243 citation statements)
references
References 45 publications
30
208
2
1
Order By: Relevance
“…For example, increased light levels cause warmer temperatures, which also directly affect X arag (higher temperature increases X arag by decreasing aragonite solubility). Some studies have found a significant relationship between coral calcification and temperature (e.g., Marshall and Clode 2004;Reynaud et al 2004;Silverman et al 2007), while others have not (e.g., Shaw et al 2012). To some extent, a positive relationship between temperature and calcification rates may be due to the effect of temperature on seawater X arag (Silverman et al 2007;Shaw et al 2012), but this effect is relatively small (0.03 units per 2°C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased light levels cause warmer temperatures, which also directly affect X arag (higher temperature increases X arag by decreasing aragonite solubility). Some studies have found a significant relationship between coral calcification and temperature (e.g., Marshall and Clode 2004;Reynaud et al 2004;Silverman et al 2007), while others have not (e.g., Shaw et al 2012). To some extent, a positive relationship between temperature and calcification rates may be due to the effect of temperature on seawater X arag (Silverman et al 2007;Shaw et al 2012), but this effect is relatively small (0.03 units per 2°C).…”
Section: Introductionmentioning
confidence: 99%
“…Though field data are limited, correlation between calcification rates and temporal variability in seawater temperature, light, and X arag have been observed on coral reef ecosystems at diurnal (e.g., Suzuki et al 1995;Halley 2003, 2006;Price et al 2012) and seasonal (e.g., Silverman et al 2007;Manzello et al 2008;Bates et al 2010;Shamberger et al 2011;Albright et al 2013) timescales. However, the interdependence of these parameters makes deciphering the relative importance and the principle driving mechanism(s) difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous experimental and field studies show that increasing CO 2 and decreasing aragonite saturation state (X ar ) lead to decreased coral calcification rates and increased dissolution rates of carbonate substrates, the predicted point in time at which an individual reef ecosystem will shift from net accretion to net dissolution varies across studies and ecosystems (Silverman et al 2007;Ohde and van Woesik 1999;Langdon et al 2000Langdon et al , 2003Andersson et al 2009;Shamberger et al 2011;Shaw et al 2012;Andersson et al 2014). While the global distribution of coral reefs is governed by light availability, temperature, nutrients and X ar (Kleypas et al 1999), at the local scale, the conditions that determine coral reef calcification, distribution and community composition are much more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ability of coral reefs to accumulate CaCO 3 at a rate greater or equal to the sum of mechanically, biologically and chemically mediated erosion rates will and may already be severely compromised as a result of ocean acidification. Silverman et al (2007) combined observed values of seasonally varying G net , Ω arag and temperature in a Red Sea coral reef ( Fig. 1) with laboratory experiment results of inorganic aragonite precipitation kinetics (Burton and Walter, 1987) and formulated a reef community rate equation:…”
mentioning
confidence: 99%
“…Where, A c is the fraction of live coral coverage in the reef; K r is the three-dimensional to planar conversion factor for reef surfaces actively precipitating CaCO 3 ; both the rate coefficient K and the order of reaction n are temperature dependent (Burton and Walter, 1987) and formulated in Silverman et al (2007); D is the diurnal average dissolution rate, estimated from the mean nighttime CaCO 3 loss. If K r , A c and D remain constant then changes in G net are proportional to the changes in the inorganic component of equation (3), i.e.…”
mentioning
confidence: 99%